Body dysmorphic disorder with fatal outcome: a case report - Cruzado, Lizardo (2010)
We report the case of a young man with body dysmorphic disorder who, as a result of his condition, remained isolated at home for three years with significant deterioration of his functionality and eventually committed suicide. Body dysmorphic disorder is an underdiagnosed condition, prognosis and treatment are complex, and should be considered as differential diagnosis in various psychiatric disorders, skin complaints and cosmetic surgery.